Housing policy in Argentina: Reflections on a decade of progressive social policy - Di Virgilio, Maria Mercedes (2017)
In 2003, the federal housing policy was launched in Argentina, marking a new era in housing policy in Latin America’s fourth most populous country. The Federal Housing Plan (FHP) sought to improve upon the complex scenario left by the deep socio-economic crisis of 2001–2002 with the most ambitious and progressive housing plan in Argentine history. This paper reviews the design and implementation of the FHP in the city of Buenos Aires and Greater Buenos Aires between 2003 and 2014. It focuses on the main characteristics of the Plan, as well as each of its subprogrammes and the paper reflects upon the main challenges encountered during implementation.